Pengaruh Variasi Roller dan Spring CVT Terhadap Konsumsi Bahan Bakar Pada Motor Matik 115 CC - Agustin, Rafly; Putri, Fenoria; Sani, Almadora Anwar (Politeknik Negeri Sriwijaya, Indonesia, 2024)
Variations of roller weights of 7 grams, 9 grams and 10 grams applied variation of the CVT spring from the standard, pressure strength 10 – 15%, as well as pressure strength 20% has an impact on fuel consumption. Because more gasoline or fuel is consumed in the combustion chamber on larger engine turns, this phenomenon occurs. Effect of fuel consumption on the use of roller weight variation using CVT spring variation on engine rotation variation. So as a whole the test data from the table as well as from the graphs can be taken that the best fuel consumption or efficiency, then the best choice is a roller of 10 grams using a standard spring at RPM 3000 yielding 11.33 ml/min and in RPM 6000 yields 23.50 ml / min rather than using a pressure spring strength of 10 – 15% and 20% even when the engine turns high at 9000 RPM that is 46.10 ml / minute rarely done using such RPM because of motorcycles used for day – day